2014
DOI: 10.1002/dac.2853
|View full text |Cite
|
Sign up to set email alerts
|

Design of a user anonymous password authentication scheme without smart card

Abstract: Summary Recently, Jiang et al. and He et al. independently found security problems in Chen et al.'s remote user authentication scheme for non‐tamper‐proof storage devices like Universal Serial Bus stick and proposed improvements. Nonetheless, we detect that the schemes proposed by Jiang et al. and He et al. overlook a user's privacy. We also observe that Jiang et al.'s scheme is vulnerable to insider attack and denial of service attacks and lacks forward secrecy. We point out that the password changing facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Authentication is, thus, the process of verifying the identity of a user as part of a system's access control to protect the information stored within them [1]. Various authentication techniques have been proposed in literature, such as text passwords [2,3], smart cards [4,5], and biometrics [6][7][8]. All of the mentioned techniques belong to distinct authentication factors.…”
Section: Introductionmentioning
confidence: 99%
“…Authentication is, thus, the process of verifying the identity of a user as part of a system's access control to protect the information stored within them [1]. Various authentication techniques have been proposed in literature, such as text passwords [2,3], smart cards [4,5], and biometrics [6][7][8]. All of the mentioned techniques belong to distinct authentication factors.…”
Section: Introductionmentioning
confidence: 99%
“…While it has been found that the password-based singleserver authentication protocols always risk in stolen-verifier attack, because the server has to maintain a password related table. Thus, the smart card, as a second security factor, gets widely used [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…They have become an important criterion of an ideal remote authentication scheme. Most of remote user authentication schemes [4,[40][41][42] are designed and evaluated according to them, while none of the schemes could actually satisfy them simultaneously. Therefore, many researchers begin to pay more attention to e a l 2 Password dependent 3 No verification table 4 Freely chosen password by the users 5 F o r w a r d s e c r e c y 6…”
Section: Introductionmentioning
confidence: 99%